Transformation of Islamic Education Management Nomenclature: Opportunities and Challenges at IAIN Curup - Jumira Warlizasusi; Ifnaldi; Irfan Qowwiyul Aziz Alhajj; Fathur Rizki (Ta'dib, 2025)
The change in the nomenclature of the Islamic Education Management Study Program (MPI) to Educational Management (MP) or Educational Administration (AP) at Islamic Religious Universities (PTKI) has had a significant impact on the development of higher education, especially within the Curup State Islamic Institute (IAIN). The aim of this research is to analyze the impact of changes in nomenclature on the management of study programs, curriculum, as well as the opportunities and challenges faced by students and alumni. The method used case study is a qualitative approach with descriptive analysis, collecting data through interviews with lecturers, students, alumni and study program managers. This study employs a qualitative descriptive–interpretative analysis to explore the transformation of Islamic education management nomenclature at IAIN Curup. The analysis focuses on understanding meanings, rationales, and implications behind nomenclature changes rather than measuring causal relationships. The research results show that changes in nomenclature open opportunities for graduates to be more accepted in non-Islamic educational institutions and expand job opportunities, but also create challenges related to the loss of Islamic identity in the curriculum and management of study programs. Apart from that, curriculum adjustments and unclear regulations regarding the acceptance of ASN and PPPK are the main issues that must be faced. This research suggests the need for strategies to maintain a balance between developing a more general curriculum and preserving the values of Islamic education in the study program.